2016
DOI: 10.1590/0370-44672016690001
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical modeling in gold deposit through DC Resistivity and Induced Polarization methods

Abstract: Ore mining fundamentally depends on the definition of its tenor and volume, something extremely complex in disseminated mineralization, as in the case of certain types of deposits of gold and sulfites. This article proposes the use of electrical tomography for definition of a geophysical signature in terms of electrical resistivity and chargeability, in an outcrop of mineralized quartz lode at the end of an inactive gold mine. One of the targets was to analyze the continuity of the mineralized body, the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…From the lateral interpolation, patterned lines generated images in three dimensions -pseudo-3D, procedure adopted in some scientific articles (Moreira & Ilha, 2011;Moreira et al, 2012;Moreira et al, 2016a;Moreira et al, 2016b;Vieira et al, 2016& Côrtes et al, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…From the lateral interpolation, patterned lines generated images in three dimensions -pseudo-3D, procedure adopted in some scientific articles (Moreira & Ilha, 2011;Moreira et al, 2012;Moreira et al, 2016a;Moreira et al, 2016b;Vieira et al, 2016& Côrtes et al, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Moreira et al . [ 22 ] show how the application of resistivity and IP supplied data for modelling of a gold deposit. Coelho et al .…”
Section: Methodsmentioning
confidence: 99%
“…From the two maps, it is observed that zones associated with high resistivity are also associated with high values of apparent chargeability. This means that there is a possibility of presence disseminated minerals hosted in rocks with high electrical resistance which is typical to hydrothermal alteration (Fon et al 2012, Moreira et al 2016). These include disseminated gold, pyrite and chalcopyrite minerals hosted in a massive quartz vein (Fon et al 2012, Moreira et al 2016.…”
Section: Resistivity Maps Of Hydrothermal Zones Resistivity and Chargeability Gradient Mapsmentioning
confidence: 99%